2004
DOI: 10.1055/s-2004-812889
|View full text |Cite
|
Sign up to set email alerts
|

Quantifizierung von Atelektasen bei kontrollierter Beatmung: Spiral-CT versus dynamische Einzelschicht-CT

Abstract: The results of our study demonstrate that dCT allows monitoring of atelectasis formation in response to different ventilatory strategies. However, a deviation between dCT and spiral-CT has to be taken into account. In subcarinal dCT series, hyperinflated lung areas and atelectases were overestimated due to a craniocaudal gradient of atelectases, whereas normal ventilated lung was underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Previous experiments in uninjured pigs have demonstrated that a subcarinal slice overestimates both overdistension and atelectasis and underestimates ventilated regions [9], in contrast with our results. Interestingly, the overdistended regions represented a significantly smaller fraction of the slice/lung volume in our study compared with those previously described (0.6% in dCT vs 1.2% in the whole lung as compared with 6.4% in dCT vs 3.1% in the whole lung in published results [9]). A possible reason for this discrepancy is that our study used 5 mm instead of 1-mm-thick CT slices.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous experiments in uninjured pigs have demonstrated that a subcarinal slice overestimates both overdistension and atelectasis and underestimates ventilated regions [9], in contrast with our results. Interestingly, the overdistended regions represented a significantly smaller fraction of the slice/lung volume in our study compared with those previously described (0.6% in dCT vs 1.2% in the whole lung as compared with 6.4% in dCT vs 3.1% in the whole lung in published results [9]). A possible reason for this discrepancy is that our study used 5 mm instead of 1-mm-thick CT slices.…”
Section: Discussioncontrasting
confidence: 99%
“…Authors of studies reporting tidal variations in parameters consistent with a decrease in CT density and atelectasis during inspiration can be reassured these are outside the limits of error introduced by the dCT technique and therefore represent true (patho)physiology. Overall, these results are confirmatory of previous findings [9, 10], extend the agreement to DECT indices and further explore the effects of inspiration with morphological analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations